Perancangan Film Dokumenter Kebudayaan Suku Sasak Desa Bayan - Yudha Delonix (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2019)
Television shows are currently dominated by programs such as reality shows, infotainment, etc. This situation inspiring Kompas TV to give different shows. Information and education are the main things that want to be presented to viewers. Through the “Explore Indonesia – Sasak Tribe” program, viewers are invited to know more closely and clearly about the cultures in various parts of Indonesia. “Explore Indonesia” is a documentary genre show. Documentary video is the most appropriate media to display a cultural reality and visual and audio. The Sasak tribe is one of the interesting cultures in Indonesia. Traditional houses, arts, and the daily lives of the unique Sasak people make this tribe a tourist attraction on the island of Lombok.